Is menstruation obsolete? - Coutinho, Elsimar M. (Oxford University Press, 1999)
The authors argue that regular monthly bleeding is not the "natural" state of women, and that it actually places them at risk of several medical conditions of varying severity. They maintain that while menstruation may be culturally significant, it is not medically meaningful.